Sales Growth, Company Size, Profitability, and Non-Debt Tax Shield on Capital Structure In Food and Beverage Sub-Sector Companies Listed on The Indonesia Stock Exchange - Nicholas Renaldo; Christian Rusli; Suhardjo Suhardjo; Suharti Suharti; Tandy Sevendy (JRAK: Journal of Accounting Research and Computerized Accounting, 2023)
This study aims to determine the effect of sales growth, company size, profitability, and non-debt tax shield on the capital structure of food and beverage sub-sector consumption companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This study used secondary data. The sampling technique in this study used purposive sampling. The number of samples obtained amounted to 38 companies. Data analysis in this study used quantitative descriptive and several calculations using the SmartPLS software. From this study, it can be concluded that only the non-debt tax shield significantly affects capital structure. While sales growth, company size, and profitability do not have a significant effect on capital structure.